Effect of the problem-based adolescent reproductive health module on students’ life skills and attitudes - Desak Made Citrawathi; Abu Yazid Abu Bakar; Putu Budi Adnyana; Ni Luh Putu Manik Widiyanti; I Ketut Sudiana (Jurnal Cakrawala Pendidikan, 2022)
This study aimed to analyze the effect of the implementation of a problem-based adolescent reproductive health module on students’ life skills and positive attitudes toward reproductive health. It was quasi-experimental research by applying a randomized pretest-posttest control group design, involving junior high school students who were divided into two groups, namely experimental and control groups. The data collection was conducted by using a life skills test and an attitude scale questionnaire as instruments. The instrument validity was tested by applying the Lawshe formula. The instrument’s reliability was tested using the Alpha-Cronbach formula. Multivariate Analysis of Variance was used to analyze the data collected. The research results indicated that learning by using a problem-based adolescent reproductive health module had a positive impact on the students' life skills and attitudes toward their reproductive health. Learning about the human reproductive system by using the module motivates the students to search for answers to the questions given at the beginning of the material. Based on those findings, learning using this module is recommended as one program to teach students (adolescents) education on reproductive health.